Characterisation of two novel ferrocenyl benzoxazines as in vitro triple-negative breast cancer inhibitors - Mhlanga, Richwell (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
Thesis access embargoed. Expected released date early 2025.
Keywords: Uncatalogued